Differences in the behaviour of model and non-model species of ants in interactions with the pod-sucking myrmecomorphic bug, Riptortus linearis (Hemiptera: Alydidae) - Joy Nivedita SAMUEL (Institute of Entomology, Biology Centre, Czech Academy of Science, 2021)
Ants are common invertebrate models of many myrmecomorphic arthropods since they are unpalatable and pose a threat for many species. Natural habitats harbour a diverse community of different species of ants and their mimics. The myrmecomorphic bug, Riptortus linearis uses a variety of extrafloral nectary-bearing or hemipteran-harbouring legumes as host plants, which are also visited by various sugar-loving species of ants. In the present study, we investigated the responses of the ant-mimicking and non-mimicking stages of the pod-sucking bug, Riptortus linearis, its ant model, Camponotus compressus and a co-occurring ant, Crematogaster subnuda, during experimental encounters, under laboratory conditions. Cr. subnuda ants were much more aggressive than Ca. compressus ants towards the myrmecomorphic bug. However, the pod-sucking bug exhibited similar responses to both of the species of ants. More importantly, Ca. compressus ants did not bite the first instar nymph of the bug. The results of this study show that the non-model ant was significantly more aggressive than the ant model towards different stages of R. linearis. These results have important implications for the management of the pod-sucking bug, R. linearis, which is an important pest of many legumes.